LGBT rights in Africa - Lise Rakner; Siri Gloppen (Edward Elgar Publishing, 2020)
This innovative and thought-provoking Research Handbook explores not only current debates in the area of gender, sexuality and the law but also points the way for future socio-legal research and scholarship. It presents wide-ranging insights and debates from across the globe, including Africa, Asia, Eastern Europe and Australia, with contributions from leading scholars and activists alongside exciting emergent voices.
English
Keywords: queer; Law; Africa; Sexuality; LGBT rights; feminism; Gender; socio-legal; LGBT